Korean Celebrity Brand Ambassador as a Strategy to Increase Sales of PT. Shopee Indonesia (Study: “Gfriend” In Shopee 11.11 Big Sale) - Rezki Pratami; Afrina Sari (MediaTor (Jurnal Komunikasi), 2020)
This article examines PT. Shopee Indonesia's strategy in increasing sales with Korean celebrity brand ambassadors. Theory used is the integrated marketing communication theory by Kotler & Armstrong (2008) and brand ambassador concept owned by Rossita & Percy (2005). Data analysis is with observation, documentation and interviews of 4 informants by applying case study methods. The results showed choosing GFRIEND as the brand ambassador of Shopee 11.11 Big Sale campaign resulted in the sale of 70 million items sold on November 11, 2019, and sales tripled in the first hour compared to 2018. By running four of eight integrated marketing communication models by Kotler & Armstrong (2008) such as sales promotion, advertising, interactive marketing, and also events and experiences conducted through both mass media, online media, and social media resulted in a third quarter achievement of 2019 PT. Shopee Indonesia increased by 261,1% or equivalent to 257,2 million dollars, as well as Gross Merchandising Value (GMV) of 69,9% or equivalent to 4,6 billion dollars compared to 2018. This means that making GFRIEND as a brand ambassador Shopee 11.11 Big Sales is the right strategy and successfully brings PT. Shopee Indonesia to a significant increase in sales.